Dietary sodium sulfate supplementation improves eggshell quality, uterine ion transportation and glycosaminoglycan synthesis in laying hens - Kai-bo Fu; Dong Dai; Jian-min Zhou; Jing Wang; Hai-jun Zhang; Shu-geng Wu; Guang-hai Qi; Jing Wang (Animal Bioscience)
Objective This study evaluated the effects of dietary sodium sulfate (Na2SO4) supplementation on eggshell quality, uterine ion transportation, and glycosaminoglycan (GAG) synthesis. Methods A total of 432 48-wk-old Hy-line Brown laying hens were randomly divided into 6 dietary treatments with 8 replicates of 9 birds each. The experimental laying hens were fed the corn-soybean meal diets (containing 0.15% NaCl) supplemented with 0.22%, 0.37%, 0.52%, 0.68%, 0.83%, or 0.99% Na2SO4 for 12 weeks. Results Results showed that the eggshell breaking strength and eggshell ratio significantly increased in the 0.68% Na2SO4 group at the end of wk 56 and wk 60 (p<0.05). In addition, eggshell thickness and weight significantly increased in the 0.68% Na2SO4 group at the end of wk 60 (p<0.05). Eggshell calcium content in the 0.68% Na2SO4 group was higher than that of 0.22% and 0.99% groups (p<0.001). The concentrations of K+ and Ca2+ in the uterine fluid were significantly greater in the 0.68% group than in the other groups (p<0.05). Dietary Na2SO4 increased the gene expression of SLC8A1, SCNN1A, ATP1B1, and KCNMA1 quadratically in the uterus (p<0.05), and higher values were observed in 0.68% group. Additionally, the GAG contents of the eggshell, and ATP-sulfurylase, sulfotransferase, chondroitin sulfate, and dermatan sulfate contents of the isthmus increased linearly with the increment of dietary Na2SO4 (p<0.05). There was a remarkable reduction in mammillary knob width, mammillary thickness, and the percentage of the mammillary layer (p<0.05), and an increment in mammillary knob density, effective thickness, and total thickness in the 0.68% group compared with the 0.22% and 0.99% groups (p<0.05). Conclusion Overall, there was no dose-related difference with the increment of dietary Na2SO4 levels. The addition of 0.68% Na2SO4 in the corn-soybean basal diet (0.15% Cl) regulated uterine ion transport, increased GAG contents of eggshell, and improved eggshell ultrastructure and quality.